518 Late-Breaking: Effect of Feedlot Diets on Environmental Emissions from Four Representative U.S. Feedlots and the Beef Production System. (8th October 2021) - Gilreath, Jessica; Rotz, Al; Place, Sara; Thoma, Greg; Wickersham, Tryon
Abstract: Our objective was to evaluate effects of feedlot dietary management strategies on environmental impacts and net returns of feedlot operations in the United States. Representative feedlots were simulated with the Integrated Farm System Model (IFSM 4.6; USDA-ARS, University Park, PA) to quantify baseline environmental impacts of feedlot production and full US beef cattle production systems. The simulated dietary strategies included: 10% increase in feed efficiency, use of less water intensive forages, 10% increase in byproduct inclusion, 10% improvement in water use efficiency of corn, and steam-flaking of corn. Days on feed and head finished per year were held constant for all strategies to have equal comparisons to baseline results. Dietary management strategies were individually modeled and simulated in IFSM for each feedlot operation to obtain intensities (expressed per kg gain) for greenhouse gas (GHG) emissions, fossil energy use, blue water consumption, and reactive nitrogen loss. Feedlot operations were then linked with cow-calf, stocker, and backgrounding operations to estimate environmental intensities (expressed per kg CW) for full cattle production systems. Improving feed efficiency had the greatest effect on reducing carbon emission intensities (6%), energy use intensity (8%), blue water use intensity (9%), and reactive N loss intensity (4%) for feedlot operations. Increasing corn byproduct inclusion resulted in 9% reduction in blue water use intensity. However, byproduct inclusion increased reactive N loss intensity by 11% as a result of greater protein concentrations in the diet. Switching from rolled corn to steam flaked corn increased energy use intensity by 9%, but little to no changes (1% increase to 3% reduction) were observed for other environmental intensities. Improved feed efficiency was the most effective strategy to reduce environmental footprints of beef cattle production (1 to 2% reductions). Overall, feedlot dietary strategies were less pronounced for the full beef production system compared with feedlot results.